New frontiers in mining complex patterns : 5th International Workshop, NFMCP 2016, held in Conjunction with ECML-PKDD 2016, Riva del Garda, Italy, September 19, 2016, Revised selected papers /: 5th International Workshop, NFMCP 2016, held in Conjunction with ECML-PKDD 2016, Riva del Garda, Italy, September 19, 2016, Revised selected papers. (2017) - Unknown
No abstract available